A case report: mechanical mitral valve thrombosis in pregnancy. Issue 1 (7th March 2019) - Rozestraten, Fleur F J; Wilcox, Ian; Lalande, Stéphanie; Simmons, Lisa A
Abstract: Background: Pregnancy in women with mechanical valves has a high risk of both valve thrombosis and bleeding as well as adverse effects on the foetus. There is limited data on achieving optimal anticoagulation in pregnancy and management of valve thrombosis, to achieve a successful foetal outcome, while prioritizing the mother's health. While warfarin may carry a lower risk of valve thrombosis, warfarin is teratogenic in the first trimester and is associated with increased foetal loss throughout the pregnancy. Heparin does not cross the placenta but is associated with increased maternal morbidity and mortality. Case summary: We describe the case of a pregnant patient with thrombosis of a mechanical mitral valve presenting with an embolic stroke at 22 weeks of pregnancy. The stroke was treated with clot retrieval and resulted in no residual neurological deficit. Two previous pregnancies had been managed with low molecular weight heparin, and both resulted in foetal loss. The patient was determined to continue this pregnancy. She was treated with intravenous unfractionated heparin during the remainder of the pregnancy. She developed worsening heart failure due to persisting valve thrombosis despite maintenance of therapeutic anticoagulation. The patient deteriorated rapidly prior to a planned early elective delivery. Emergency Caesarean section was required followed by valve replacement using extracorporeal membrane oxygenation support with an ultimately successful maternal and foetal outcome. Anticoagulation regimes and treatment of mechanical valve thrombosis in pregnancy are discussed. Discussion: The management of pregnant patients with mechanical valves is complex, especially when valve thrombosis and other complications occur. A multidisciplinary approach is essential and in this case led to successful outcome.